Human capital, social capital, psychological capital, and job performance: Based on fuzzy-set qualitative comparative analysis - Xu, Qian; Hou, Zhe; Zhang, Chao; Yu, Feng; Guan, Jiangyue; Liu, Xiao (Frontiers in Psychology, 2022)
The present study investigated the configuration effect of human capital, social capital, and psychological capital on job performance. The human capital questionnaire, social capital scale, psychological capital scale, and job performance scale were used to survey 458 employees. Results revealed that four antecedent configurations could achieve high task performance, and three antecedent configurations can achieve high contextual performance. The high job performance driving path was characterized by “all roads lead to Rome.” Human capital, social capital, and psychological capital affected job performance in the form of configuration, which reflected the asymmetric causal relationship.